Numerical and Experimental Study of CPU Cooling with Finned Heat Sink and Different P.C. Air Passages Configurations - Jalil, Jalal M.; Ali, Ekbal H.; Kurdi, Hiba H. (Al-Nahrain Journal for Engineering Sciences, 2018)
This study investigated numerically and experimentally fluid flow and heat transfer in the desktop PC. Three patterns of the positions of air inlet and outlet were tested to find the best one for cooling. The computer components in the present study are CPU, finned heat sink, power supply, motherboard, CD, HDD and fans. Three components which were generate heat are CPU, motherboard and power supply and there were two openings for air inlet and two for air outlet. The air inlet velocities were 1.2, 1.8, 2.4 m/s with constant CPU fan velocity. The studied parameters were the changed of inlet air velocity, powers of CPU, motherboard and PSU and the positions of inlet air. The numerical results obtained are found in a good agreement with the experimental results. The experimental results show that the maximum temperature was 81 at 16.5 W and 1.2 m/s. Numerical results showed that the CPU temperature reaches 89.6 at 18.5 W and 1.2 m/s. From the results, it was found that; the temperatures of the main components (PSU and motherboard) affected little by CPU power and vice versa, the finned heat sink has higher cooling efficiency and the pattern 1 was the best pattern for CPU cooling.